Design and analysis of MEMS high sensitive capacitive pressure sensor - Ali, M.; Soin, N.; Noorakma, A.C.W.; Yusof, N.; Hatta, S.F.W.M. (Medwell Journals, 2016)
In this study, MEMS high sensitive capacitive pressure sensor based on poly-silicon diaphragm have been designed and analysed by using COMSOL Multiphysics Software. Three sensor designs: clamped, 8 slotted and 4 slotted with and without Teflon (polytetrafluoroethylene) coating were tested and compared to understand the sensitivity and deflection of the sensors. The pressure sensor was designed to evaluate the pressure in ranges of 0-60 mmHg which is in the range of Intraocular Pressure (IOP) for glaucoma. The capacitive pressure sensor is design using different structures of the diaphragm and it is identified that 4 slotted square diaphragms gives the highest sensitivities amongst the presented design. By coating the diaphragm and adding slots into the diaphragm, the displacement improves while mechanical and capacitance sensitivities increase.